Multi-scale interface design of strong and damage resistant hierarchical nanostructured materials. (November 2020) - Daniel, Rostislav; Meindlhumer, Michael; Zalesak, Jakub; Baumegger, Walter; Todt, Juraj; Ziegelwanger, Tobias; Keckes, Julius F.; Mitterer, Christian; Keckes, Jozef
Abstract: Synthesis of damage resistant nanostructured materials with high strength and fracture toughness is a challenging task. In this work, multi-scale interfaces were implemented into a hierarchical TiN/SiOx microstructure to mimic stepwise crack growth behaviour of the hard and damage resistant bivalve mollusc Saxidomus purpuratus shell. In situ micromechanical testing in scanning and transmission electron microscopes revealed multi-scale crack deflection events at grain boundaries of individual alternately-tilted TiN crystallites, at kinks of their repeatedly tilted columnar grains as well as crack interaction with perpendicular interfaces of elastic amorphous SiOx layers. These events induced an increase in the crack surface area, reduction of the crack driving force and dissipation of local stress and energy at the crack tip with subsequent crack slow-down or arrest, resulting in fracture toughness exceeding by ~200% the toughness of monolithic TiN nanoceramics. By this perspective biomimetic microstructural design, catastrophic failure of brittle ceramics may be turned into a predictable and controllable process increasing reliability of strong materials in various challenging safety-critical engineering applications. It also shows potential paths for the development of strong and simultaneously tough materials with high mechanical and thermal stability. Graphical abstract: Unlabelled Image Highlights: The structural complexity of hierarchical TiN/SiOx ceramic resulted in a fracture toughness enhancement of more than 200%. A multiscale hierarchical architecture allows for activation of multiple extrinsic toughening mechanisms, which turn catastrophic failure into a controllable process. Nanostructured ceramics can be simultaneously strong and tough even while combining brittle constituents. The biomimetic approach applied for ceramic materials is specifically promising for high-temperature applications.